The Mental Health Mandate: Evaluating the Legal Requirement for Psychological Support Services within Higher Education Institutions - Nurphi, Meiria (Indonesian Journal of Education and Youth Development, 2026)
As global reports indicate clinically significant levels of mental disorder symptoms among university students, higher education institutions (HEIs) are increasingly positioned as front-line mental health responders. However, the legal basis for this expectation remains fragmented and contested. This study employs a dual-method approach, qualitative doctrinal analysis and a systematic literature review, to evaluate the legal mandates for psychological support in the US, UK, and EU. Findings indicate that while a universal right to therapy is absent, a de facto mandate has emerged through disability and equality laws, which categorize mental health support as an enforceable "reasonable accommodation" rather than a discretionary welfare service. The research explores the shift from in loco parentis to organizational risk management, highlighting the evolution of "duty of care" in the context of student suicide and foreseeable harm. Synthesizing these findings, the study identifies a persistent gap between statutory access requirements and actual clinical needs, often exacerbated by the friction between privacy laws (HIPAA/FERPA) and fragmented administrative systems. The research concludes that HEIs must transition from purely defensive, risk-averse practices toward standardized, proactive governance to meet evolving legal obligations and ensure equitable participation in higher education.